Konseling Multibudaya di Sekolah - Erlamsyah Erlamsyah (Seminar Konseling 2017, 2017)
Interactions between children or students of different cultural backgrounds gives their the opportunity to learn and share their cultural wealth of the nation, and the interaction of different cultures children can give rise to difficulties and conflicts when lacking awareness of multicultural; justify its own culture and ignore or deny other people's culture. Multicultural atmosphere in school in order to become wealth and is not a problem for students, schools need to develop multicultural awareness so that they can receive the child's own culture and respect for the culture of others, and can foster harmonious relations between different cultural. The schools will also need to provide service to children from different cultures in order to avoid various problems, and help them develop optimally in all the dimensions of their development. One of the services to help children of diverse cultures at the school is through a multicultural counseling services. Multicultural counseling services through the child helped develop awareness, respect the child against his own culture and culture of others, and learning the fundamental principles of cultural diversity. Supervising teacher or counselor needs to implement multicultural counseling to help children in order to avoid problems and to give them a chance of realizing the self development of optimally as individuals.This article discusses the multicultural counseling in schools. The focus of the discussion in this paper concerns the notion of culture, understanding multicultural counseling, multicultural counseling goals, awareness of multicultural counselor, a multicultural counselor competencies, multicultural counselors roles and efforts to increase awareness of multicutural counselor.